The Role of E-learning in Studying English Language: Teachers’ and Students’ Perspectives - Tiwari, Hari Prasad (Nepal Journal of Multidisciplinary Research, 2022)
The substantial increase in technological innovation over the past few decades has had a significant impact in the field of English Language Teaching (ELT). Governments throughout the world are investing a lot of resources to keep up with this technological innovation as a result. Considering this, many local levels of Nepal recently committed to implement e-learning to teach English and other subjects in schools and colleges. Keeping this in mind, the present descriptive phenomenological study tries to explore English Language (EL) teachers’ and students’ perceptions regarding the role of E-learning in studying English. A total of 24 participants including eight EL teachers and 16 students studying English Education at master’s level participated in the study. I employed convenience technique to collect the study area and purposive sampling technique to select the sample. Similarly, I employed the Single Focused Group Disunion (SFGD) technique to collect the data. As per the choice of the participants, the discussions were conducted in the Nepali language in face-to-face mode. FGDs were audio recorded, transcribed and thematized. The findings of the study were presented and discussed in terms of themes using descriptive methods for analyzing qualitative data. The findings are presented and explored in four themes. They are promoting fundamental learning skills, independence, adaptability, and interaction.